As questões de gênero na formação inicial de docentes: tensões no campo da educação - Unbehaum, Sandra G. (2014)
This research deals with teachers training, and particularly focuses on the training of teachers for basic education. The study sought to gain an understanding in the aspects involved on the inclusion of gender issues into the curriculum of teachers training in the classroom, specifically in pedagogy courses offered by Brazilian public universities. It was assumed that despite a suitable environment gender is already a consolidated field of research and there are educational policies favorable to it the issues related to this field have only a secondary status in the curriculum of teacher's training. It was hypothesized that there are tensions and resistance movements in the general field of education, which implies, therefore, the need of more articulation of those two fields (education and gender), in order to the second be able to influence the curriculum of teacher's training. Through interviews, a total of eleven university research-teachers participated in this study, eight of them been women. All the subjects were linked to public universities, where they taught in graduate and undergraduate courses; they were also leaders and co-leaders of research groups, in programs in which gender is one of the main topics of interest. It was possible to conclude that have been advances in the introduction of gender in teachers training, with this theme receiving a crossing approach in regular disciplines as well as in the proposition of elective or optional courses. Moreover, it was noted a lack of agreement in establishing the content of gender as an obligatory discipline or as a transversal one. Conflicts in relation to theoretical conceptions of the field, impacting on the spheres of academic debate, were found